Enhanced NOLC1 promotes cell senescence and represses hepatocellular carcinoma cell proliferation by disturbing the organization of nucleolus. Issue 4 (10th May 2017) - Yuan, Fuwen; Zhang, Yu; Ma, Liwei; Cheng, Qian; Li, Guodong; Tong, Tanjun
Summary: The nucleolus is a key organelle that is responsible for the synthesis of rRNA and assembly of ribosomal subunits, which is also the center of metabolic control because of the critical role of ribosomes in protein synthesis. Perturbations of rRNA biogenesis are closely related to cell senescence and tumor progression; however, the underlying molecular mechanisms are not well understood. Here, we report that cellular senescence‐inhibited gene (CSIG) knockdown up‐regulated NOLC1 by stabilizing the 5′UTR of NOLC1 mRNA, and elevated NOLC1 induced the retention of NOG1 in the nucleolus, which is responsible for rRNA processing. Besides, the expression of NOLC1 was negatively correlated with CSIG in the aged mouse tissue and replicative senescent 2BS cells, and the down‐regulation of NOLC1 could rescue CSIG knockdown‐induced 2BS senescence. Additionally, NOLC1 expression was decreased in human hepatocellular carcinoma (HCC) tissue, and the ectopic expression of NOLC1 repressed the proliferation of HCC cells and tumor growth in a HCC xenograft model.